ANALISIS SUPPLY BAGI STANDAR MANAJEMEN PENGEMBANGAN DI KAWASAN EKOWISATA RAJA AMPAT (*) - Wiriadi Sutrisno (JABE (Journal of Applied Business and Economic), 2015)
Tourism industry is one of the economic sub-sector that is able to contribute Government revenue,  after Oil and Gas  (MIGAS) export. Raja Ampat is a Tourism Destination Region  (DTW) featured  by this time,  which is rich with  coral reefs. However, the wealth of biodiversity has made itself high level of threat as well. It can be seen from damage to coral reefs and forests, due to fishing activities which are not environmental friendly such as bombs, cyanide and roots bore.         Phenomenon in the world of tourism is showing a favorable prospects of the business side. This industry market conditions indicate a "sustainable profit values", namely a number of value sustainable advantage. Raja Ampat as DTW, has a diversity of attractions that can improve local communities welfare , by stimulating PAD even by foreign tourists visits  with dollar allocation. But the achievements of Raja Ampat DTW not maximized, still far below Bali, even Bunaken.            Therefore, it is worth actually done  thorough analysis of the condition of the tourism market, especially on the supply side, market actors, stakeholders (government, NGOs and local communities) and the condition of the surrounding environment.